Rancang Bangun Sistem Informasi Manajemen Bank Sampah Studi Kasus Pada Bank Sampah Panggung Berseri (BSPB) - Veri Julianto; Hendrik Setyo Utomo; Herpendi (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
Waste is the result of the dynamics of life that can cause problems if it is not properly managed. Many methods had been used to help overcome waste management. The Waste Bank is one of the solutions to help solve waste management. Bank Sampah Panggung Berseri is one of the communities that actively carries out waste management around the Pangung village. BSPB has problems related to solid waste management. The management in question is the management of waste data that is still conventional, archiving is not optimal, has not managed customer data savings properly. In this research also added a marketplace feature where people can make transactions from balances obtained from waste sold by buying basic necessities. The method in this research is to collect data at BSPB, analyze data and develop applications using the prototype method. The results of this study are all the features or functions of the system run well by testing the functionality used the Black Box testing method. In testing using the usability testing method has shown the level of satisfaction for the parameters of usability, ease of learning, ease of use and satisfaction gives an average value of 4.38 from the range of values ​​1-5. This shows that the system made can be said to satisfy BSPB users and customers.